1977
DOI: 10.1037/0033-2909.84.1.173
|View full text |Cite
|
Sign up to set email alerts
|

The myth of perceptual defect: Sources and evidence.

Abstract: A hypothesis of a perceptual defect in black populations, suggested tentatively 20 years ago, was found to be still alive in the research literature. The hypothesis, its original data base, and more recent literature were examined. It was found that the hypothesis did not distinguish between the effects of race versus early experience on perceptual functioning. Reflecting this confusion, the original data base for the hypothesis was seriously flawed. Many studies assumed that the hypothesis could be demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
1988
1988

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…For example, some groups may demonstrate lower levels of performance on tests of fluid intelligence as compared to tests of crystallized intelligence. The theory behind such dis-tinctions is weak (see, for example, Mandler & Stein, 1977;Sherman, 1978) and the evidence is inconsistent (Arvey, 1972). If the item types and tests used were also differentially subject to practice effects, then the inconsistency in results becomes explicable.…”
Section: Pects Of Intelligence?mentioning
confidence: 99%
“…For example, some groups may demonstrate lower levels of performance on tests of fluid intelligence as compared to tests of crystallized intelligence. The theory behind such dis-tinctions is weak (see, for example, Mandler & Stein, 1977;Sherman, 1978) and the evidence is inconsistent (Arvey, 1972). If the item types and tests used were also differentially subject to practice effects, then the inconsistency in results becomes explicable.…”
Section: Pects Of Intelligence?mentioning
confidence: 99%
“…In a recent review of research on perceptual memory tasks Mandler and Stein (1977) suggested that few, if any, ethnic differences had been demonstrated. However, one of the recurrent features of pattern reproduction studies in the cross-cultural setting has been the higher frequency of orientation errors produced by non-western samples.…”
Section: Discussionmentioning
confidence: 99%